Можливості застосування сучасних САТ-інструментів у діяльності перекладача - Король, Антоніна Анатоліївна; Бузила, Карина Володимирівна (Міжнародний гуманітарний університет, 2023)
The article is devoted to the study of the possibilities of modern CAT tools in the work of a translator. The article considers the working stages of the modern translation process and the corresponding CAT tools available in the translation arsenal. The research material consists of 10 user manuals for kitchen appliances from wellknown German manufacturers (mixer, blender, food processor, meat grinder, coffee maker, multicooker, bread maker, etc.) and their translations into Ukrainian.The following research methods were used to achieve the goal and solve the tasks: the observation method was used to determine the main stages of the translation process and the use of optimal software for their automation; analysis method was employed to determine the functionality of the software and the feasibility of its usage for automating term extraction and the creation of a bilingual glossary based on a corpus of parallel texts; descriptive method was used to provide a detailed description of each stage of the investigated process. A search for materials was conducted to compile a mini-corpus and prepare the entire array of selected bilingual corpora for aligning parallel texts using the LF Aligner program in the *txt UTF-8 format to create a translation memory. The advantages and disadvantages of the automated term extraction process were identified using the online resource Sketch Engine from a self-created corpus of parallel texts of user manuals for kitchen appliances to compile a bilingual glossary in this field. The Sketch Engine online resource not only automatically extracts potential terms from the corpus but also displays their frequency of use in the selected (e.g., created) and reference corpora, as well as allows analyzing the contexts of the extracted nominations. It has been established that the program only facilitates certain processes of translator preparation for translation orders but is unable to fully automatically generate a bilingual dictionarythesaurus without involving human resources. The research resulted in the compilation of a German-Ukrainian glossary of technical terms based on bilingual parallel text corpora using the Sketch Engine online resource in a format suitable for use in automated translation systems such as Matecat, MemoQ, WordFast, Déjà Vu, WorldServer, MultiTrans, LogiTerm, OmegaT, MemSource, etc.
Стаття присвячена дослідженню можливостей сучасних САТ-інструментів у діяльності перекладача. Розглянуто робочі стадії сучасного перекладацького процесу і відповідні САТ-інструменти, наявні в перекладацькому арсеналі.
Keywords: CAT tools, parallel text corpus, term and term combination, dictionary-thesaurus